Penguatan Literasi Work-Life Balance melalui Psikoedukasi bagi Personel Kepolisian - Sayang Ajeng Mardhiyah; Annisa Sri Maharani (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
Work-life balance is an important aspect to be considered in the police profession, which is characterized by high work demands. Psychoeducation on work-life balance was conducted to improve police officers’ understanding of the importance of maintaining balance between work and personal life. The participants in this activity were 19 police officers from Polda Sumsel. Pretest and posttest analyses were carried out using JASP version 0.95.3.0 with the Wilcoxon Signed Rank Test. The results showed that the data were not normally distributed, therefore the Wilcoxon test was applied, yielding a significance value of p = 0.000 (p < 0.05). The findings indicated a difference in the mean scores between the pretest and posttest, where the post-test mean was higher than the pretest (9.63 > 6.37). This increase in understanding shows that psychoeducation is effective in providing knowledge regarding the importance of maintaining a balance between work and personal life. Furthermore, similar psychoeducation programs can be implemented on an ongoing basis within the police environment.